2018
DOI: 10.1016/j.eurpsy.2018.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Changes in attitude towards LAI antipsychotic maintenance treatment: A two-year follow-up study

Abstract: The switch to LAI-AMT may help to address the subjective core of an optimal recovery in stabilized schizophrenic patients. A sustained improvement in patients' attitude towards drug may help to achieve patient's compliance. The size of this study needs to be expanded to produce more solid and generalizable results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 47 publications
(124 reference statements)
1
20
0
Order By: Relevance
“…Poor adherence to medication is a significant problem in the treatment of schizophrenia, and is a frequent cause of illness relapse, hospitalisation and worsening of the patient's symptoms and function [1]. Several studies have investigated the pros and cons of oral medication versus long acting medication through injections (LAI) [2][3][4][5][6][7][8][9]. Compared to oral antipsychotic treatment, LAI significantly increases the time to symptomatic relapse and re-hospitalisation and reduces mortality [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Poor adherence to medication is a significant problem in the treatment of schizophrenia, and is a frequent cause of illness relapse, hospitalisation and worsening of the patient's symptoms and function [1]. Several studies have investigated the pros and cons of oral medication versus long acting medication through injections (LAI) [2][3][4][5][6][7][8][9]. Compared to oral antipsychotic treatment, LAI significantly increases the time to symptomatic relapse and re-hospitalisation and reduces mortality [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Although some large randomized controlled trials (RCTs) have not shown significant difference in efficacy between LAIs and oral antipsychotics,5,6 the experimental nature of RCTs, such as enhanced compliance and selective recruitment, might explain these results. In naturalistic settings, several studies have demonstrated the superior effectiveness of LAIs over oral antipsychotics in improving quality of life, reducing hospitalization rates and treatment discontinuation;7,8 however, LAIs remain underutilized in clinical practice 9,10. To date, patients’ and psychiatrists’ attitudes toward LAIs that may affect clinical practice have been investigated 11,12.…”
Section: Introductionmentioning
confidence: 99%
“…In current clinical practice, LAIs are often reserved for non-adherent patients, and psychiatrists themselves avoid prescribing LAIs to patients with first-episode schizophrenia [47]. While some patients prefer LAIs over OAPs due to increased relapse prevention [48] as well as better quality of life [49], others report being coerced into undergoing treatment with LAIs [50]; with pain at the injection site, misconceptions regarding LAIs, and lack of awareness also being reported as reasons for low LAI uptake [51,52]. Bridges et al [53] recently quantified the effect of schizophrenia treatment goals on a patient's treatment plan.…”
Section: Discussionmentioning
confidence: 99%